การลดสีย้อม Acid Red 2 โดยแบคทีเรีย - ปั้นเพ็ง เกตุนารินทร์; ปัณณานุสรณ์ ศรีสุดา; ธนานันต์ ธีระชัย; ศากยวงศ์ นิรมล (Thai Journal of Science and Technology, 2019)
Abstract Decolorization of Acid Red 2 dye by Lysinibacillus sphaericus (C23), Paenibacillus sp. B1 (C29), Paenibacillus sp. Dg.904 (C24) and Stenotrophomonas maltophilia (C39) was studied. From the beginning dye concentration of 100 mg L-1, the bacterial C23 could 100 % decolorize with an average rate of decolorization at 12.50 mg L-1 h-1, under static conditions at 37 oC, pH 7.0 within 8 hours. By increasing dye concentration up to 500 mg L-1, the C23 could remain 100 % decolorization, while the average decolorization rate was 25.00 mg L-1 h-1 during 20 hours. In the section of degradation product analysis by using UV-visible spectrophotometry, the maximum adsorption wavelengths were changed from 429 nm to 238 nm. The result indicated that the specific functional groups of Acid Red 2 dye were changed after biodegradation. In addition, Fourier transform infrared (FTIR) spectroscopy had analyzed the changing of functional groups of Acid Red 2 dye structure after decolorization. The functional groups of the products after decolorization were smaller than those of the original Acid Red 2 structure. The percentage of COD removal after decolorization by C23 was 66.18. However, the toxicity of decolorized products to green bean growth was found that the percentage of germination, plumule length, and radical length increased significantly when compared with those of Acid Red 2. Keywords: Acid Red 2 dye, decolorization, Lysinibacillus sphaericus